Kritik Sosial dalam Karya Sastra Bentuk Nyata Protes Sastrawan - Neneng Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to describe social criticism, a real form of man of letters protest against social problems throughher/his literary media. The method used is descriptive method. The results of this study found that Wisran Hadi and Athur S. Nalan conveyed their dislike of social phenomena through drama scripts. This is what is meant by the real form of literary protests through his work. Wisran Hadi through the drama drama